Species identification and phylogenetic relationships among five species of psocids from Chinese herbal medicines. (January 2020) - Li, Mengnan; Yang, Qianqian; Shao, Huangfang; Sun, Entao; Zheng, Lingxiao; Sun, Mengtao; Chen, Yingwei; Huang, Wenyu; Ye, Changjiang; Liu, Liu; Lu, Ying; Fang, Weixi
Abstract: The main objectives of the study were to establish an accurate multiplex PCR identification technique for five species of psocids from Chinese herbal medicines and to discuss the phylogenetic relationships among those species. Five species of booklice ( Liposcelis bostrychophila, L. entomophila, L. tricolor, L. pearmani and L. rufa ) were collected from Chinese herbal medicines. Genomic DNA of individual booklice was obtained via a nondestructive DNA extraction method. The internal transcribed spacer (ITS)1-5.8S-ITS2 gene sequences were obtained by PCR amplifying and sequencing. The primers were designed, and the phylogenetic trees were constructed using the NCBI website and MEGA software. In this research, a Multiplex PCR identification technique was established based on the ITS2 gene for the five species of booklice. The phylogenetic relationships among the five booklice species were analyzed and discussed based on the ITS gene sequences. Highlights: There is a mixture of booklice contamination in herbal fragments. Multiplex PCR identification was established to identify L. pearmani and L. rufa. ITS gene sequence is suitable for inferring phylogeny among Liposcelis in this study.